DEVELOPING CRITICAL THINKING IN CHILDREN AGED 3–7 THROUGH PROBLEMATIC SITUATIONS (Лучшие интеллектуальные исследования, 2025)
Abstract: Critical thinking is a fundamental skill that supports children’s cognitive, social, and emotional development. This article explores the methods and benefits of fostering critical thinking skills in children aged 3 to 7 by engaging them in problematic situations. Through carefully designed activities and guided questioning, young learners develop the ability to analyze, evaluate, and solve problems creatively.